Circular RNA circ_0006168 accelerates the development of hepatocellular carcinoma through sponging microRNA-125b: Circ_0006168 promotes HCC - Zhuang, Linjun; He, Chenxin; Gao, Jiawei; Zhu, Zhaobi; Lin, Changjie; Chen, Wei (Cellular and Molecular Biology, 2024)
This study explored the role of circular RNA circ_0006168 in the progression of hepatocellular carcinoma (HCC) and its interaction with microRNA-125b. The expression of circ_0006168 was examined in 42 pairs of HCC tumor and adjacent tissue specimens using quantitative polymerase chain reaction (qPCR). Elevated circ_0006168 expression in HCC tissues was significantly associated with advanced pathological staging and lower overall survival rates. Lentivirus-mediated circ_0006168 knockdown in HCC cell lines (Hep3B and Huh7) demonstrated a notable reduction in cell proliferation and an increase in apoptosis. MicroRNA-125b expression exhibited a marked reduction in HCC tissues, negatively correlating with circ_0006168 levels. Luciferase reporting assays indicated that circ_0006168 was a direct target of microRNA-125b. Additionally, cell recovery experiments suggested a reciprocal regulation between circ_0006168 and microRNA-125b, contributing to the accelerated malignant progression of HCC. The study underscored the significantly increased expression of circ_0006168 in both HCC tissues and cell lines, highlighting its association with advanced pathological stages and poor prognosis in HCC patients. Furthermore, circ_0006168 appeared to play a pivotal role in elevating the proliferation rate of HCC cells through its modulation of microRNA-125b. These findings contribute to a deeper understanding of the molecular mechanisms underlying HCC development and may offer potential therapeutic targets for intervention.